Quaternionic Version of Rotation Groups and Lorentz Group - Rahmawati, Latief; Khalif, Muhammad Ardhi; Rosyid, Muhammad Farchani (JOURNAL OF NATURAL SCIENCES AND MATHEMATICS RESEARCH, 2015)
Quaternionic version of rotation groups and Lorentz Group has been constructed. The rotation groups that has been discussed were quaternionic version of groups , O(3), and SO(3). The Lorentz groups that has been discussed were quaternionic version of groups SL(2;C), O(3; 1), and SOo(3; 1). Starting from the definition of each group, the parameters of the group were obtained. Finally the generators of the group were obtained. The commutation of the generator were also computed.Â